Application of Electrical Resistance Tomography in an Oscillatory Baffled Column for Gas-Liquid Two-Phase Flow - Abdul Rahim, Ruzairi; Hamzah, Ahmad Azahari; Takriff, Mohd Sobri; Mohamad, Elmy Johana; Pusppanathan, Jaysuman; Azman, Intan Norjahan; Mohd Ghazali, Mohd Syazwan; Sabri, Mohamad Zulkeflee; Ghafar, Faridah; Zahari, Mohd Nizam (International Journal of Integrated Engineering, 2019)
Oscillatory baffled column (OBC) has a high potential for industrial application especially contacting gas and liquid phase. However, there are still lacks of research regarding the dynamics of gas-liquid phase specifically on the visualization of internal flow. Electrical Resistance Tomography (ERT) technique has capabilities to visualize mixing process internally without invading the flow. The objective of this study is to investigate the gas-liquid mixing distribution in an OBC by applying tomography technique model ITS P2000 of ERT system. The parameters investigated are phase distribution, gas hold up and power density. The experimental work was carried out in an OBC with a diameter of 145 mm and 720 mm height. The column is consisted of four planes of sixteen stainless steel ERT electrodes. The results of the research have shown that 70 mm of oscillation amplitude and 2 Hz of oscillation frequency give the best result with 73% of gas hold up and 12433.39W/m3.